Chapter "Noi leggiavamo un giorno per diletto": Reading Dante in South Africa - Fanucchi, Sonia (Studi e saggi, 2021)
Since its conception in 2018, our Dante society has evolved to embrace a unique, South African engagement with the poet and his Commedia. This chapter provides an insight into the society's origin and the conversations that first inspired our South African Convivio with Dante. Through a detailed description of the thinking behind the contributions of students and colleagues, we highlight the process of reading Dante as a powerful personal experience for us and our students. We argue that Dante provides us with a language through which to make sense of our vulnerable position in post-Apartheid South Africa. This is evident in the ways that student responses to Dante echo the Commedia's Dante-Virgil dynamic - complex, and sometimes rebellious, yet always intimate and affectionate.